CDKN2A Deletion Leading to Hematogenous Metastasis of Human Gastric Carcinoma - Qiao, Juanli; Tian, Yuan; Cheng, Xiaojing; Liu, Zhaojun; Zhou, Jing; Gu, Liankun; Zhang, Baozhen; Zhang, Lianhai; Ji, Jiafu; Xing, Rui; Deng, Dajun (Frontiers in Oncology, 2021)
Introduction: Somatic copy number deletion (SCND) of CDKN2A gen is the most frequent event in cancer genomes. Whether CDKN2A SCND drives human cancer metastasis is far from clear. Hematogenous metastasis is the main reason of human gastric carcinoma (GC) death. Thus, prediction GC metastasis is eagerly awaited. Method: GC patients (n=408) enrolled in both a cross-sectional and a prospective cohorts were analysed. CDKN2A SCND was detected with a quantitative PCR assay (P16-Light). Association of CDKN2A SCND and GC metastasis was evaluated. Effect of CDKN2A SCND by CRISPR/Cas9 on biological behaviors of cancer cells was also studied. Results: CDKN2A SCND was detected in 38.9% of GCs from patients (n=234) enrolled in the cross-sectional cohort. Association analysis showed that more CDKN2A SCND was recognized in GCs with hematogenous metastasis than those without (66.7% vs. 35.7%, p=0.014). CDKN2A SCND was detected in 36.8% of baseline pN0M0 GCs from patients (n=174) enrolled in the prospective study, the relationship between CDKN2A SCND and hematogenous metastasis throughout the follow-up period (62.7 months in median) was also significant (66.7% vs. 34.6%, p=0.016). Using CDKN2A SCND as a biomarker for predicting hematogenous metastasis of GCs, the prediction sensitivity and specificity were 66.7% and 65.4%. The results of functional experiments indicated that CDKN2A SCND could obviously downregulate P53 expression that consequently inhibited the apoptosis of MGC803 GC and HEK293T cells. This may account for hematogenous metastasis of GCs by CDKN2A SCND. Conclusion: CDKN2A SCND may drive GC metastasis and could be used as a predictor for hematogenous metastasis of GCs.